Characteristics of users of the Birth Control program. - Lalinde Ángel, María Isabel; Molina M, Gloria; Olarte L, Martha Lucia (Investigación y Educación en Enfermería, 2013)
<!-- [if gte mso 9]> <![endif]--> Objective. This study sought to characterize the use of Birth Control methods by women users of Healthcare Service Provider Institutions in Colombia, who were included in the National Health Survey -2007 NHS. Methodology. Ours was a descriptive study, which performed secondary analysis of the data from a subsample of 2033 women from the outpatient service of the Birth Control (BC) program in the Healthcare Service Provider Institutions (IPS, for the term in Spanish) included in the 2007 National Health Survey (NHS). Results. The BC contraception methods most used by the women surveyed were: hormonal (60%), barrier (22%), and female sterilization (11%). A direct relationship was observed between educational level and the autonomy to select the BC method. A total of 11% of the users did not receive information on all the BC methods from their treating physician. Some 98% of the women surveyed manifested having understood the information provided on the use of the BC method selected. Nine of every 10 women exercised autonomy upon selecting a BC method. Conclusion. The hormonal methods of Birth Control were the most used by the women surveyed. The participants showed high autonomy to choose the BC method. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->